PENINGKATAN KETERAMPILAN DAN JIWA WIRAUSAHA PADA YAYASAN BHAKTI SENANG HATI DI DESA SIANGAN, GIANYAR, BALI - Utami Nilawati Ni Ketut; I Gde Eka Dharsika; Ketut Laksmi Maswari (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
A disability foundation is an organization established to provide support, services, and resources to individuals with disabilities. The goal of these foundations is typically to improve the quality of life for people with disabilities through various programs, such as education, skills training, empowerment, accessibility, and advocacy for their rights. Disability foundations also play a vital role in raising public awareness about the importance of being open to accepting and accommodating diversity in society, as well as equal access for all. The Bhakti Senang Hati Foundation is a non-profit organization located in Siangan Village, Gianyar, Bali, Indonesia. The foundation focuses on empowering and supporting people with disabilities, particularly those with hearing impairments, both children and adults. Its primary goal is to provide education, skills training, and access to health and social services so that individuals with disabilities can live independently and participate in society. Through its community service activities, the Bhakti Senang Hati Foundation provides entrepreneurship training and donations of basic food supplies. It is hoped that through these community service activities, the Bhakti Senang Hati Foundation will help improve the welfare of its members.